Sub-national Public Private Partnerships in Kenya: an appraisal of the legal and institutional framework against the constitutional principles on devolution and public procurement - Rono, Naphtaly Kipchirchir (Strathmore University, 2021)
The study appraises the legal and institutional framework for sub-national PPPs in Kenya with a view to assessing their conformity with the constitutional principles on devolution and public procurement, and by extension, their impact on the adoption of sub-national PPPs by county governments in Kenya. The conformity with the identified constitutional principles and efficacy of the legal and institutional framework is assessed through the lenses of Economic Analysis of Law Theory as well as the Soufflé Theory. The study evaluates the legal and institutional framework for sub-national PPPs in Kenya and identifies the gaps and deficits therein. It also evaluates the legal and institutional framework for Sub-national PPPs in comparative jurisdiction. The above-mentioned legal appraisal, survey and comparative analyses largely confirm the hypotheses of the study, which are, that the procurement regime and institutional framework established under the PPPs Act is not in conformity with the constitutional principles on devolution, and to some extent, with some of the constitutional principles on public procurement; that the existing legal and institutional framework is not efficacious and is partly to blame for the low adoption of sub-national PPPs in Kenya. Arising from the findings, the study recommends appropriate reforms of the legal and institutional framework for sub-national PPPs in Kenya. It also recommends for enhancement of capacity and credibility of county governments to undertake PPPs. Finally, the recommends for further research on areas not covered by the present study.
A Thesis submitted in partial fulfillment of the requirements of the Degree of Master of Laws, at Strathmore University
Keywords: Public Private Partnerships (PPPs); Constitutional principles; Devolution; Public procurement